2017
DOI: 10.3389/fcimb.2017.00147
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Distribution of Putative Virulence and Colonization Factors in Shiga Toxin-Producing Escherichia coli Isolated from Different Categories of Cattle

Abstract: Shiga toxin-producing Escherichia coli (STEC) are pathogens of significant public health concern. Several studies have confirmed that cattle are the main reservoir of STEC in Argentina and other countries. Although Shiga toxins represent the primary virulence factors of STEC, the adherence and colonization of the gut are also important in the pathogenesis of the bacteria. The aim of this study was to analyze and to compare the presence of putative virulence factors codified in plasmid -katP, espP, subA, stcE- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Constable had reported that the bacteria toxins exerts effect on the thermoregulatory center of the hypothalamus thereby altering the thermostatic level. The other clinical signs such as heart rate, respiratory rate, capillary refilling time, weakens, dehydration is similar to those observed and reported by Constable et al; Cundon et al; Caceres et al (9,22,23). These authors reported that the production of the enterotoxin results in net secretion of fluid and electrolytes from the systemic circulation into the lumen of the intestine, resulting in varying degrees of diarrhea, dehydration, electrolyte imbalances, acidemia, circulatory failure, shock, and death.…”
Section: Discussionsupporting
confidence: 90%
“…Constable had reported that the bacteria toxins exerts effect on the thermoregulatory center of the hypothalamus thereby altering the thermostatic level. The other clinical signs such as heart rate, respiratory rate, capillary refilling time, weakens, dehydration is similar to those observed and reported by Constable et al; Cundon et al; Caceres et al (9,22,23). These authors reported that the production of the enterotoxin results in net secretion of fluid and electrolytes from the systemic circulation into the lumen of the intestine, resulting in varying degrees of diarrhea, dehydration, electrolyte imbalances, acidemia, circulatory failure, shock, and death.…”
Section: Discussionsupporting
confidence: 90%
“…Some factors that contribute to the presence and spread of STEC in a herd are the management practices, stress, diet, population density, geographic region and season [41]. Contact with feces of cattle, direct contact with the animals or their environment and consumption of contaminated beef, milk, dairy products, water, unpasteurized apple juices and vegetables are possible routes for STEC human exposure and disease [42]. So, measures to prevent direct contact with animal fecal material in the environment include the wearing of protective clothing, increased hand washing and targeted education of the population at risk regarding possible sources of STEC infection.…”
Section: Discussionmentioning
confidence: 99%
“…Obtained data suggest that BoNT/A, in addition to altering neuronal function, can also influence spinal microglial cells [ 38 , 39 ]; however, it is still unclear whether those BoNT/A actions are mediated in a direct or indirect manner. The latest in vitro research by Piotrowska et al 2017 [ 62 ] shed new light on the analgesic effect of BoNT/A and suggested a possible direct impact of this toxin on microglia in the CNS ( Figure 1 ).…”
Section: Mechanism-based Evidence For the Analgesic Actions Of Bonmentioning
confidence: 99%
“…The direct influence of BoNT/A on astroglia was unclear, since the study by Parpura et al (1995) [ 64 ] showed the expression of some of the SNARE protein complexes but not that of SNAP-25. The authors analyzed post-nuclear astroglial cell membrane extract, not the whole lysates as in Piotrowska et al 2017 [ 62 ]. The authors, using in vitro primary cell culture studies, have demonstrated that astroglial cells possess both mRNA and protein for the SNAREs SNAP-25 and SNAP-23 [ 62 ].…”
Section: Far Beyond the Neurons—the Role Of Glial Cells In Bont/a-mentioning
confidence: 99%
See 1 more Smart Citation